Deformation of Threaded Metal – Composite Couplings Under the Action of Gas-Dynamic Loads - Kostiantyn V. Avramov; Maryna V. Chernobryvko; Volodymyr V. Kombarov; Sergiy I. Plankovskyy; Yevgen V. Tsegelnyk (Journal of Mechanical Engineering)
The combination of metal and composite in threaded couplings increases the reliability of the structure operating under conditions of intensive internal pressure. Strength analysis of threaded metal – composite couplings based on the application of modern finite element modeling methods at the stage of design documentation development allows to create more efficient structures that better meet the operational requirements. The strength of threaded couplings of cylindrical shells made of composite material and metal under the action of gas-dynamic internal pressure is analyzed in this paper. A methodology for numerical study of the problem in Ansys / Explicit Dynamics software package is proposed. Detailed modeling of threaded couplings is used. The developed model takes into account the following: dependence of material properties on ambient temperature; nonlinear relations between the components of stress and strain tensors in metal elements, orthotropic properties of composite materials; peculiarities of contact interaction in the zones of threaded couplings of prefabricated shell elements made of different materials. The stress state of a cylindrical structure with a central shell made of carbon fiber-reinforced plastic or fiberglass and with steel shells at the edges, loaded with gas-dynamic internal pressure with a maximum value of 20 MPa at a maximum ambient temperature of 100 °С was studied. It was obtained that plastic deformations are concentrated on the edges of the threaded couplings of steel shells. At the same time, the magnitude of plastic coupling deformations with the inner metal shell is an order of magnitude higher than for couplings with the outer metal shell. The magnitude of plastic deformations in couplings with an inner metal shell is twice less when using fiberglass than when using carbon fiber reinforced plastic. Localization of critical stresses was observed only in metal shells at threaded couplings. In this case, in the thread zone they are within the elasticity limits, and the stress state of the FRP shell is not critical. No local material failure was observed in the structure.